Concise Review: Induced Pluripotency by Defined Factors: Prey of Oxidative Stress. (May 2015) - Qi, Suxia; Fang, Zhi; Wang, Danli; Menendez, Pablo; Yao, Ke; Ji, Junfeng
Abstract: Reprogramming somatic cells to pluripotency (induced pluripotent stem cells, iPSCs) via forced expression of defined factors has become one of the most fascinating areas in biomedical research because it holds a tremendous application potential for cell therapy, disease modeling, and drug screening applications. However, cellular reprogramming is a very inefficient and metabolically demanding process commonly associated with genomic instability of the resulting iPSCs. Low reprogramming efficiency and presence of de novo genomic aberrations in iPSCs may hamper their downstream applications. Here, we review mounting studies that have tackled reprogramming efficiency and genome stability of iPSCs. In particular, we focus on the effect of oxidative stress on cellular reprogramming. We will discuss how oxidative stress influences cellular reprogramming and the mechanisms by which antioxidants promote reprogramming efficiency and preserve genome integrity of iPSCs. A reduction of oxidative stress is expected to augment reprogramming efficiency and concomitantly promote the genomic integrity of the resulting iPSCs, eventually facilitating the implementation of cellular reprogramming for downstream applications. Stem Cells 2015;33:1371–1376